2010
DOI: 10.1128/jb.00672-10
|View full text |Cite
|
Sign up to set email alerts
|

Bathy Phytochromes in Rhizobial Soil Bacteria

Abstract: Phytochromes are biliprotein photoreceptors that are found in plants, bacteria, and fungi. Prototypical phytochromes have a Pr ground state that absorbs in the red spectral range and is converted by light into the Pfr form, which absorbs longer-wavelength, far-red light. Recently, some bacterial phytochromes have been described that undergo dark conversion of Pr to Pfr and thus have a Pfr ground state. We show here that such so-called bathy phytochromes are widely distributed among bacteria that belong to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
91
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 44 publications
(57 reference statements)
2
91
2
Order By: Relevance
“…In particular, 3 increases, and 2 decreases. The value of 4 , the time constant characterizing the dark reaction within the first 4 s (after switching off the pre-illumination at 785 nm), is almost doubled between pH 6 and 9.…”
Section: Titration Of Agp2: Uv/visiblementioning
confidence: 99%
See 2 more Smart Citations
“…In particular, 3 increases, and 2 decreases. The value of 4 , the time constant characterizing the dark reaction within the first 4 s (after switching off the pre-illumination at 785 nm), is almost doubled between pH 6 and 9.…”
Section: Titration Of Agp2: Uv/visiblementioning
confidence: 99%
“…Spectral properties of six members of this group (Agp2, Avp1, Avp2, and phytochromes of Rhizobium leguminosarum, Rhizobium etli, and Azorhizobium caulinodans) have been characterized by in vivo photometry and studies on recombinant proteins (3). All of these phytochromes with the exception of Avp1, which displays unusual spectral properties, are bathy phytochromes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 To whom correspondence may be addressed. (17) as well as other rhizobial species (18). Early studies on plant phytochromes have shown that the fluorescence quantum yield of Pr is low at ambient temperature but is increased significantly under cryoconditions where photoconversion is blocked (19).…”
mentioning
confidence: 99%
“…This different stability of the parent states is most probably the reason why three-dimensional structures so far have been mainly obtained for the Pr state of protypical phytochromes and the Pfr state of bathy phytochromes (13)(14)(15)(16)(17)(18)(19)(20). Although the gross chromophore structures in the respective parent states are likely to be similar in prototypical and bathy phytochromes, it appears to be premature to consider the available three-dimensional structures of the Pr states of the prototypical phytochrome and the yet only available three-dimensional structure of the Pfr state of bathy phytochrome from Pseudomonas aeruginosa (PaBphP) as representative structures for the respective parent states in both classes of phytochromes (12).…”
mentioning
confidence: 99%